Manajemen Peserta Didik Dalam Membentuk Karakter Siswa Religius Di SMP Islam Nurul Khalil Bondowoso - Mohammad Irfan Efendi; Mohamad Yahya (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2023)
Student management is an arrangement of all student activities related to the initial entry so that students leave. Student activities are an important part of an educational institution. Student management and religious character have a relationship, namely religious character must be instilled early on to students in the process the formation of the religious character of students will not take place by itself, but the process is influenced by the school environment. The focus of the problems examined in this thesis are: 1) How is the Planning of Student Admission in the Formation of Religious Character at SMP Islam Nurul Khalil Bataan Tenggarang Bondowoso? 2) How is the Development of Students in the Formation of Religious Character at SMP Islam Nurul Khalil Bataan Tenggarang Bondowoso? The approach in this research is descriptive qualitative. Data collection techniques using three methods namely, observation, interviews and documentation. Checking the validity of the data using source triangulation and method triangulation. Sources of research data include school principals, curriculum deputy heads, teachers and students. The results of this study are: (1) describing the planning of student admissions in the formation of religious character at Nurul Khalil Islamic Middle School, namely in planning students in forming religious character at Nurul Islamic Middle School Khalil covers three things, namely: 1) Establishing 8 Student Character standards 2) Forming Religious Character 3) Providing Supporting Facilities, and forming a committee for accepting new students, disseminating information on new student admissions and selecting prospective students. (2) describing the development of students in the formation of religious character at Nurul Khalil Islamic Middle School, namely by getting used to activities that already exist in junior high schools such as requiring students to take part in recitation activities every morning, praying in congregation and the school principal enforcing 5S (Greetings, Smiles, Greetings, Polite , polite) so that students can appreciate and respect each other. Manajemen peserta didik merupakan suatu penataan segala aktifitas siswa yang berkaitan dengan awal masuk sehingga keluarnya peseta didik.Kegiatan peserta didik merupakan bagian penting dari suatu lembaga pendidikan.Manajemen peserta didik dan karakter religius memiliki hubungan yaitu karakter religius harus ditanamkan sejak dini kepada peserta didik dalam proses pembentukan karakter religius peserta didik tidak akan berlangsung dengan sendirinya, akan tetapi proses tersebut dipengaruhi oleh lingkungan sekolah. Fokus masalah yang diteliti dalam skripsi ini adalah: 1) Bagaimana Perencanaan Penerimaan peserta didik dalam Pembentukan Karakter religius di SMP Islam Nurul Khalil Bataan Tenggarang Bondowoso? 2) Bagaimana Pembinaan Peserta Didik dalam Pembentukan Karakter Religius di SMP Islam Nurul Khalil Bataan Tenggarang Bondowoso? Adapun pendekatan dalam penelitian ini adalah kualitatif yang bersifat deskriptif. Teknik pengumpulan data menggunakan tiga metode yakni, observasi, wawancara dan dokumentasi. Pengecekan keabsahan data menggunakan triangulasi sumber dan triangulasi metode. Sumber data penelitian diantaranya adalah kepala sekolah, waka kurikulum, guru dan Peserta didik Hasil penelitian ini yaitu: (1) mendeskripsikan perencanaan penerimaan peserta didik dalam pembentukan karakter religius di SMP Islam Nurul Khalil yaitu Dalam perencanaan Peserta didik dalam pembentukan karakter religius di SMP Islam Nurul Khalil mencakup tiga hal yaitu: 1) Menetapkan 8 standart Karakter Siswa 2) Membentuk Karakter Religius 3) Menyediakan fasilitas Pendukung, danmembentuk panitia penerimaan peserta didik baru, menyebarkan inormasi penerimaan peserta didik baru dan menyeleksi calon peserta didik. (2) mendeskripsikan pembinaan peserta didik dalam pembentukan karakter religius di SMP Islam Nurul Khalil yaitu dengan membiasakan kegiatan yang sudah ada di SMP seperti mewajibkan siswa untuk mengikuti kegiatan mengaji disetiap pagi, sholat berjamaah dan kepala sekolah memberlakukan 5S (Salam, Senyum, Sapa, Sopan, Santun) agar peserta didik dapat menghargai dan menghormati sesama.